2017
DOI: 10.1186/s13058-017-0851-4
|View full text |Cite
|
Sign up to set email alerts
|

Mutation site and context dependent effects of ESR1 mutation in genome-edited breast cancer cell models

Abstract: BackgroundMutations in the estrogen receptor alpha (ERα) 1 gene (ESR1) are frequently detected in ER+ metastatic breast cancer, and there is increasing evidence that these mutations confer endocrine resistance in breast cancer patients with advanced disease. However, their functional role is not well-understood, at least in part due to a lack of ESR1 mutant models. Here, we describe the generation and characterization of genome-edited T47D and MCF7 breast cancer cell lines with the two most common ESR1 mutatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
184
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 124 publications
(209 citation statements)
references
References 28 publications
25
184
0
Order By: Relevance
“…The D538G mutation, observed in ~20% of patients with AI-treated metastatic breast cancers 9,12,20,22 , in the h11–12 loop of the ERα LBD, has constitutive activity comparable to or somewhat less than that of Y537S (Figure 2B) 24,27,28 . Structural data shows that the charged D538 residue in WT apo-ERα introduces a kink in the protein backbone driven by its strong preference for solvent exposure and electrostatic repulsion from other nearby acidic residues (e.g., D351), and it initiates the helical character at the start of h12 16 .…”
Section: [Introduction]mentioning
confidence: 99%
“…The D538G mutation, observed in ~20% of patients with AI-treated metastatic breast cancers 9,12,20,22 , in the h11–12 loop of the ERα LBD, has constitutive activity comparable to or somewhat less than that of Y537S (Figure 2B) 24,27,28 . Structural data shows that the charged D538 residue in WT apo-ERα introduces a kink in the protein backbone driven by its strong preference for solvent exposure and electrostatic repulsion from other nearby acidic residues (e.g., D351), and it initiates the helical character at the start of h12 16 .…”
Section: [Introduction]mentioning
confidence: 99%
“…Thus, in T47D cells, Y537S elicited a more endocrine-resistant phenotype, whereas in the MCF7 cell background the Y537S and D538G mutant ERs were more similar to each other in their response to antiestrogens. This suggests that cell context, including alterations in genomic and cell signaling pathways, may work with ERs to confer different cell behaviors and responsiveness or resistance to treatment with different endocrine agents (23,31,32). This is not surprising, since it is known, for example, that among other differences, MCF7 and T47D cells carry different mutant forms of PI3K.…”
Section: Discussionmentioning
confidence: 99%
“…T47D cells with both mutant ERα alleles were generated by CRISPR-Cas9 technology and mutation status of the clonal cell lines was verified by genotyping as described before (21). MCF7 cells or T47D cells containing 50% mutant Y537S- or D538G-ERα and 50% wild type ERα, determined by DNA sequencing and digital drop PCR analyses as detailed previously (17,23), were generated by adenovirus associated viral infection (MCF7) or CRISPR-Cas-9 methodology (T47D) (17,21,23,24). These cells were cultured as described(17,21,23,24).…”
Section: Methodsmentioning
confidence: 99%
“…[20][21][22] Using in vitro-derived ESR1 mutant cell line models generated using CRISPR/Cas9 technology, or through natural selection of cells in hormone-deprived conditions, Martin et al 23 showed that there was a high overlap between ER chromatin binding sites of estrogen-stimulated WT receptor and hormone-deprived mutant receptors. [20][21][22] Using in vitro-derived ESR1 mutant cell line models generated using CRISPR/Cas9 technology, or through natural selection of cells in hormone-deprived conditions, Martin et al 23 showed that there was a high overlap between ER chromatin binding sites of estrogen-stimulated WT receptor and hormone-deprived mutant receptors.…”
Section: Biology Of Esr1 Mutations In Preclinical Studiesmentioning
confidence: 99%
“…The transcriptomes of WT and mutant ERs have been described by several groups, showing there are shared, classical ER signaling signatures, as well as mutant-specific transcriptional regulation. [20][21][22] Using in vitro-derived ESR1 mutant cell line models generated using CRISPR/Cas9 technology, or through natural selection of cells in hormone-deprived conditions, Martin et al 23 showed that there was a high overlap between ER chromatin binding sites of estrogen-stimulated WT receptor and hormone-deprived mutant receptors. They further showed that estrogen treatment of both the WT and Y537S models exhibited a 74% concordance in ER binding sites.…”
Section: Introductionmentioning
confidence: 99%